Анализ течения пара через сито регулирующего клапана паровой турбины К-325 на стационарном режиме роботы - Колядюк, А. С.; Шульженко, Н. Г. (НТУ "ХПИ", 2013)
Рассматривается течение пара в системе парораспределения на основе численного решение уравнений Навье-Стокса. Определяются характеристики течения пара. Применяется модель турбулентности k–ω SST Ментера. Установлены основные особенности течения пара через сито и в камере, где оно установлено

It is considered the flow of vapor in steam distribution system based on the numerical solution of Navier-Stokes equations. It is determined the defining characteristic of vapor flow. The Menter SST turbulence model is used. It is calculated the main features of the vapor flow through the screen and in the chamber, where the screen is installed
Keywords: расчет; система парораспределения; уравнения Навье-Стокса; сито; клапан; давление; calculation; flow of vapor; steam distribution system; turbine